Monovalent and trivalent VSV-based COVID-19 vaccines elicit neutralizing antibodies and CD8+ T cells against SARS-CoV-2 variants - Kate A. Parham; Gyoung Nyoun Kim; Connor G. Richer; Marina Ninkov; Kunyu Wu; Nasrin Saeedian; Yue Li; Rasheduzzaman Rashu; Stephen D. Barr; Eric J. Arts; S.M. Mansour Haeryfar; C. Yong Kang; et al. (iScience, 2023)
Summary: Recombinant vesicular stomatitis virus (rVSV) vaccines expressing spike proteins of Wuhan, Beta, and/or Delta variants of SARS-CoV-2 were generated and tested for induction of antibody and T cell immune responses following intramuscular delivery to mice. rVSV-Wuhan and rVSV-Delta vaccines and an rVSV-Trivalent (mixed rVSV-Wuhan, -Beta, -Delta) vaccine elicited potent neutralizing antibodies (nAbs) against live SARS-CoV-2 Wuhan (USAWA1), Beta (B.1.351), Delta (B.1.617.2), and Omicron (B.1.1.529) viruses. Prime-boost vaccination with rVSV-Beta was less effective in this capacity. Heterologous boosting of rVSV-Wuhan with rVSV-Delta induced strong nAb responses against Delta and Omicron viruses, with the rVSV-Trivalent vaccine consistently effective in inducing nAbs against all the SARS-CoV-2 variants tested. All vaccines, including rVSV-Beta, elicited a spike-specific immunodominant CD8+ T cell response. Collectively, rVSV vaccines targeting SARS-CoV-2 variants of concern may be considered in the global fight against COVID-19.